2017
DOI: 10.1242/dev.148460
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Chondrocytic ephrin B2 promotes cartilage destruction by osteoclasts in endochondral ossification

Abstract: There was an error published in Development 143, 648-657.In the Materials and Methods section the murine Efnb2 gene mutation was incorrectly listed as Efnb2 tm1And . The correct annotation for the floxed allele that we used in our experiments is Efnb2 tm2And . This was a nomenclature error and does not affect the results or conclusions of the paper.We thank Monika Tomczuk, scientific curator of Mouse Genome Informatics at The Jackson Laboratory, for alerting us to this mistake.We apologise for any confusion th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Rodeo et al 30 and Ma et al 25 also found that the higher osteoclastic activity at early healing stage of 1 or 3 weeks influenced the new bone formation and bony architecture at the tendon-tobone interface. Furthermore, osteoclast recruitment is likely to cause the newly formed cartilage destruction, degradation, and matrix resorption, 2,18,23,41 which might be related to the minimal cartilage formation at the interface in the OP group. Therefore, considering the possibly negative effects associated with osteoclasts, it might be helpful to control the higher osteoclastic activity at the repaired site in osteoporotic status, thus facilitating bone quality and cartilage formation for better tendon-to-bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Rodeo et al 30 and Ma et al 25 also found that the higher osteoclastic activity at early healing stage of 1 or 3 weeks influenced the new bone formation and bony architecture at the tendon-tobone interface. Furthermore, osteoclast recruitment is likely to cause the newly formed cartilage destruction, degradation, and matrix resorption, 2,18,23,41 which might be related to the minimal cartilage formation at the interface in the OP group. Therefore, considering the possibly negative effects associated with osteoclasts, it might be helpful to control the higher osteoclastic activity at the repaired site in osteoporotic status, thus facilitating bone quality and cartilage formation for better tendon-to-bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…In joints with OA, some blood vessels of the subchondral bone can penetrate calcified cartilage and even invade non-calcified cartilage ( Chen et al, 2015 ). Osteoclast precursors invade the area of hypertrophic cartilage and interact with its cells to reshape the cartilage matrix and form an ossification center ( Tonna et al, 2016 ). In addition, mature osteoclasts could regulate nearby chondrocytes, which destroys the connection between the bone and cartilage and degrade articular cartilage via cysteine proteases and matrix metalloproteinases ( Löfvall et al, 2018 ).…”
Section: Various Mechanisms Of Cellular Crosstalk In Oa Pathogenesismentioning
confidence: 99%
“…In bone tissue, ephrins and Ephs are widely expressed in various cells ( differentiation (109). On the contrary, ephrinB2 enhanced osteogenic differentiation through EphB4 of osteoblasts, which is a forward signaling (108,110).…”
Section: Ec-contact Regulation In Bone Biology Is Also An Important Mmentioning
confidence: 99%